The Prognostic Utility of 18F-Fluorodeoxyglucose Positron Emission Tomography-Computed Tomography-Based Analyses of Metabolic Response Rates in Newly Diagnosed Diffuse Large B Cell Lymphoma Patients - Li, Cong; Yu, Haifeng; Chen, Xi; Han, Shuiyun; Peng, Shuailing; Lei, Tao; Yang, Haiyan (Frontiers in Oncology, 2022)
Background: Roughly one third of diffuse large B cell lymphoma (DLBCL) patients experience relapsed or refractory disease, and their prognosis is unsatisfactory. It is thus important to identify patients who respond poorly to first-line treatment. Some studies have evaluated the prognostic value of interim PET-CT (iPET-CT) or end-of-treatment PET-CT (ePET-CT) in lymphoma patients, but there have been few studies exploring the prognostic value of metabolic response rates in the evaluation of DLBCL patients. Methods: Consecutive newly diagnosed DLBCL patients were screened from March 2013 to June 2020. Patients received at least four cycles of chemotherapy, and underwent baseline, iPET-CT and ePET-CT scanning. Kaplan-Meier survival curves with log-rank tests were employed to assess survival outcomes including overall survival (OS) and progression-free survival (PFS). Independent predictors of survival were identified through univariable and multivariable Cox regression analyses. Results: 307 patients were evaluated. At the time of iPET-CT scanning, 250, 45, and 12 patients exhibited complete response (CR), partial response (PR), and stable disease (SD) / progressive disease (PD), respectively. The percentage of negative iPET-CT was 81.4% (250/307). Among 295 patients with ePET-CT, 262 (88.8%) achieved negativity and 33 (11.2%) exhibited positivity including 26 PR and 7 PD. The 2-year PFS and 2-year OS for patients with iPET-CT positivity were 50.7% and 76.5%, respectively, and were significantly shorter than those for patients with iPET-CT negativity (2-year PFS 82.7%, p<0.001; 2-year OS 94.2%, p<0.001). Patients with ePET-CT positivity had significant poorer 2-year PFS (48.1%) and 2-year OS (78.5%) compared with those ePET-CT negativity (2-year PFS 83.8%, p<0.001; 2-year OS 94.9%, p<0.001). The positivity rates on iPET-CT and ePET-CT evaluation were significantly higher in patients in the high/high-intermediate risk group compared with patients in the low/low-intermediate group. In a Multivariable analysis, high/high-intermediate international prognostic index (IPI) and ePET-CT positivity were independently associated with poor PFS and OS. Conclusions: Our results suggest that the speed of metabolic response to treatment is of limited prognostic value in newly diagnosed DLBCL patients. Patients exhibiting PR at iPET-CT evaluation should carefully consider whether to change chemotherapy regimen.